A Functional Assessment Tool to DistinguishControls From Alzheimer’s Disease in Lima,Peru - Custodio, Nilton (2022)
Background:The Alzheimer’s Disease Cooperative Study-Activities of Daily Living (ADCS-ADL) scale is a versatile functionalassessment tool for patients with Alzheimer’s disease (AD). We evaluated its performance in controls, Peruvians with MCI orAD.Methods:A cross-sectional study of older adults attending a neurology institute in Lima (Peru) with mild cognitive impairment(MCI),ADor cognitively healthy. Test-retest reliability (intraclass correlation coefficient, ICC; internal consistency, Cronbach’salpha) and validity were assessed.Results:We enrolled 276 individuals (AD: 113, MCI: 68, controls: 95) with no age, sex, educational level, and depressivesymptom differences. Reliability was ideal (ICC: .996), and Cronbach’s alpha was adequate (.937). The ADCS-ADL could notdifferentiate MCI from controls but did differentiateADseverity. The ADCS-ADL correlated highly with nearly all tools.Conclusions:The ADCS-ADL scale is reliable in a population withADin Lima, Peru. Future work may validate a tool forPeruvians with lower educational levels.